VALUE DRIVERS TERHADAP NILAI PEMEGANG SAHAM PERUSAHAAN YANG HEDGING DI DERIVATIF VALUTA ASING - Fika Fitriasari (Universitas muhammadiyah malang, 2011)
Fakultas Ekonomi Universitas Muhammadiyah MalangE-mail: fika@umm.ac.idABSTRACTThe aim of this research are to understanding and analyzing the effect of value drivers variables(sale growth, operation profit, fixed asset investment, work capital investment, and capital cost) onshareholder value in the company with hedging strategy in foreign currency derivative. Result ofresearch indicates that: value drivers actually are expected to increase the shareholder value incompany with hedging strategy in foreign currency derivative; value drivers actually may increasethe shareholder value in company with hedging strategy in foreign currency derivative, capital costcannot improve shareholder value in company with hedging strategy in foreign currency derivative;and sale growth is the strongest factor to increase shareholder value in company with hedging strategyin foreign currency derivative.Key words: value drivers, shareholder value, hedging, foreign currency derivative